Video Capacity of WLANs With a Multiuser Perceptual Quality Constraint - Jing Hu; Choudhury, S.; Gibson, J.D. (IEEE transactions on multimedia, 2008)
As wireless local area networks (WLANs) become a part of our network infrastructure, it is critical that we understand both the performance provided to the end users and the capacity of these WLANs in terms of the number of supported flows (calls). Since it is clear that video traffic, as well as voice and data, will be carried by these networks, it is particularly important that we investigate these issues for packetized video. In this paper, we investigate the video user capacity of wireless networks subject to a multiuser perceptual quality constraint. As a particular example, we study the transmission of AVC/H.264 coded video streams over an IEEE 802.11a WLAN subject to a constraint on the quality of the delivered video experienced by r% (75%, for example) of the users of the WLAN. This work appears to be the first such effort to address this difficult but important problem. Furthermore, the methodology employed is perfectly general and can be used for different networks, video codecs, transmission channels, protocols, and perceptual quality measures.